PENGARUH PROBLEM BASED LEARNING (PBL) DISERTAI VIDEO TERHADAP HASIL BELAJAR PESERTA DIDIK MATERI SISTEM GERAK MANUSIA DI SMAN 1 KOTA SOLOK - Dera Despita; Helvita Roza; Ratih Komala Dewi; Darmanella Dian Eka Wati; Chairul Amri; Afrahamiryano; Irwan Hanafi; Yulhan (LPPM Universitas Ekasakti, 2024)
This research aims to determine the influence of the Problem Based Learning (PBL) Model accompanied by Video on Student Learning Outcomes on Human Movement Systems Material at SMAN 1 Solok City. This research uses a quasi-experimental method with a control class and an experimental class. The research population was students of class XI MIPA SMAN 1 Solok City, with 7 classes sampled randomly. Classes XI IPA 4 and XI IPA 7 were chosen as the experimental and control classes. The instrument used is the final test. The test results show the average score for the experimental class is 81.83 and the control class is 67.73. Statistical tests show that the learning outcomes of students taught using PBL are better than those using conventional methods. So, it can be concluded that PBL with video has a positive influence on student learning outcomes in Human Movement Systems material at SMAN 1 Solok City.